Ivacaftor in cystic fibrosis adults: Czech experience with six years of follow-up - Fila, Libor; Valentová-Bartáková, Lucie; Grandcourtová, Alžběta; Marel, Miloslav; Drnek, Radovan; Bilkova, Alena; Macek, Milan; Dřevínek, Pavel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
AIMS: Ivacaftor is a revolutionary treatment option for cystic fibrosis (CF) patients with G551D and other gating mutations. The aim of this study was to evaluate the clinical status of patients on ivacaftor who were followed for up to 6 years together with an evaluation of ivacaftor therapy in one patient with an initial FEV1 less than 40% of predicted value. METHODS: Data on development of clinical status and sinopulmonary-related therapies were obtained from patient health records during ivacaftor treatment lasting for up to six years and were compared with an equivalent period before ivacaftor administration. RESULTS: Five CF adults with a median age 28.6 years (range 21.4-35.6 years) with median FEV1 45% pred. (range 16-85% pred.) were included in the study. Four subjects were also participants in the STRIVE and PERSIST studies. Altogether, twenty-four patient-years of ivacaftor treatment were analyzed. The median FEV1 decline per year decreased from -4.5 to -0.9% pred. (P = 0.043). Reduction in number of days on antibiotic treatment and hospital stays was 21% (P < 0.001) and 75% (P = 0.003), respectively. Improvement and stabilization of lung function was observed for up to six years of treatment. In a patient with severe airway obstruction, an increase in the FEV1 value (30.4% from baseline) was documented during the first twelve months of treatment. CONCLUSION: Ivacaftor therapy resulted in improved and stabilized lung function in up to six years of treatment with a reduction in number of days on antibiotic treatment and hospital stays. Its efficiency was also displayed in a patient with severe airway obstruction.
Keywords: Aftercare; Aminophenols; Male; Forced Expiratory Volume; výsledek terapie; Quinolones; mužské pohlaví; následná péče; Adult; mladý dospělý; aminofenoly; Cystic Fibrosis; Young Adult; chinolony; ženské pohlaví; Chloride Channel Agonists; Humans; aktivátory chloridových kanálů; usilovný výdechový objem; dospělí; Female; Treatment Outcome; lidé; cystická fibróza